HYDROCARBON POTENTIAL OF THE MAIKOP SERIES - Mykhailov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Studies of the Maikop series of the southern margin of the East European platform revealed its distinct heterogeneity as to the concentration of organic matter and other gas components. It was found that the Oligocene-Early Miocene is the global era of the carbon accumulation. Formation of high-carbon strata of this level is assotiated with anoxic conditions of hydrogen sulfide contamination of water strata. Usually, Maikop sediments are characterized by high degree of bituminisation. It is believed that lower Maikop (Oligocene) deposits of the West Black See basin are graded at MK4AK1, and sediments of Tuapse, Sorokin and Guria depression are graded at MK3 (the main zone of oil generation – MZG), Upper Maikop (Lower Miocene) of the east part of the Black Sea are graded at MK1, and sediments of Tuapse, Sorokin depression, the Shatsky Swell do not reach MZG. On land, Lower Maikop deposits (Khadum suite of the Northern Precaucasia, rocks of the Kerch-Taman and West Kuban depression) show high oil source potential. In the Kerch Peninsula and Sochi-Adler depression Maikop deposits occurred at katagenesis grade PK – early MK1, that is maturing stage when the mass generation of liquid hydrocarbons has not started yet. In the Black Sea and the Crimean region the Maikop series is represented by thick layer of clay and mudstone interbedded with siltstones and sandstones, rich in organic matter (from 0,69 to 10,23 %), Corg (2,20–16,70 %). They are associated with numerous hydrocarbon fields. However, the degree of thermal transformations of rocks is very low – reflectivity of vitrinite almost everywhere does not exceed 0,36–0,60 (protocatagenesis), only rarely reaching 0,84–1,64. Thus, organic matter of the Maikop series is usually immature and characterized by relatively low temperature of pyrolysis (418–423 °C), that testifies to a shallow occurrence of the host rock (up to 1,5–2,0 km). But MZG is occurred at the depths of 3-6 km. Thus, the rocks of the Maikop series, that occur at depths of up to 2000-3000 m, as a rule, are thermally immature and cannot be treated as a prospective site for oil shale research. At the same time at the depth more than 2000–3000 m degree of thermal maturity of the rocks increase and they might be considered as prospective for oil shale research on condition of enrichment in organic matter.